Stable Carbon and Oxygen Isotopic Composition of Mio-Pliocene Bivalve Shells and Calcareous Sediments in Nhila Anticline, Southeast Bengal Basin, Bangladesh - Hossain, HM Zakir; Sultan-Ul-Islam, Md; Armstrong-Altrin, John S; Sial, Alcides N; Ahamed, Sabbir; Nowsher, Md Nahid; Abdullah-Al-Kawsar, Md (Journal of Life and Earth Science, 2014)
Stable carbon (?13C) and oxygen (?18O) isotopes of bivalve shells and calcareous sediments of the Mio-Pliocene Nhila Anticline, southeast Bengal Basin, Bangladesh have been investigated to obtain information on paleoclimate and paleoenvironment conditions during deposition. The ?13CPDB, ?18OPDB and ?18OSMOW values in bivalve shell range from -2.81 to -1.56, -3.57 to -2.39 and 27.18 to 28.40 in bivalve shells and -13.90 to -1.75, -4.71 to -2.13 and 26.01 to 28.66 in calcareous sediments, respectively. The ?13CPDB values in bivalve shells are comparable to that of calcareous sediments ( -1.75) in the upper section, but ?13CPDB values in calcareous sediments are more negative excursion towards lower section (up to -13.90). These results signify that salinity gradients could modified the isotope values and/or strong influence of freshwater conditions. The variable ?18OPDB values in both bivalve shell and calcareous sediment suggesting diagenetic alteration of carbonates and water temperature effects. The more negative ?18OPDB values imply humid paleoclimatic conditions during the Mio-Pliocene sedimentation. Therefore, the ?18OPDB values of the Mio-Pliocene sediments of Nhila Anticline are probably controlled by paleotemperature leading to intensification of high rainfall. DOI: http://dx.doi.org/10.3329/jles.v8i0.20155 J. Life Earth Sci., Vol. 8: 113-117, 2013